2014
DOI: 10.1103/physrevd.90.075003
|View full text |Cite
|
Sign up to set email alerts
|

Updated constraints on general squark flavor mixing

Abstract: We explore the phenomenological implications on nonminimal flavor violating (NMFV) processes from squark flavor mixing within the minimal supersymmetric standard model (MSSM). We work under the model-independent hypothesis of general flavor mixing in the squark sector, being parametrized by a complete set of dimensionless δ AB ij (A; B ¼ L; R; i; j ¼ u; c; t or d; s; b; i ≠ j) parameters. The present upper bounds on the most relevant NMFV processes, together with the requirement of compatibility in the choice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 69 publications
1
49
0
Order By: Relevance
“…More details about the calculations employed can be found in Refs. [13,14]. We perform our numerical calculation with the BPHYSICS subroutine taken from the SuFla code [32] (with some additions and improvements as detailed in Refs.…”
Section: B-physics Observablesmentioning
confidence: 99%
See 2 more Smart Citations
“…More details about the calculations employed can be found in Refs. [13,14]. We perform our numerical calculation with the BPHYSICS subroutine taken from the SuFla code [32] (with some additions and improvements as detailed in Refs.…”
Section: B-physics Observablesmentioning
confidence: 99%
“…We perform our numerical calculation with the BPHYSICS subroutine taken from the SuFla code [32] (with some additions and improvements as detailed in Refs. [13,14] 3.15 ± 0.23 × 10…”
Section: B-physics Observablesmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] investigated properties of the dark matter (DM) candidate, while the consequences for the Higgs mass, B-physics and electroweak (EW) observables were discussed in refs. [19][20][21][22][23].…”
Section: Jhep04(2015)120mentioning
confidence: 99%
“…[20][21][22][23]. It was shown that while m h can be enhanced by non-zero (2, 3) entries of the trilinear down-squark matrix, its dependence on the off-diagonal soft-mass elements is negligible.…”
Section: Higgs Flavour and Electroweak Observablesmentioning
confidence: 99%